The study of hillside development towards the awareness of slope department on safety and risk / Mohammad Zulamka Zamri - Zamri, Mohammad Zulamka (Faculty Architecture, Planninng and Surveying, 2015)
Hillside area are the famous area of getting near to the nature flora and fauna, this is include the view that are made people falling in love to developed the area as residential or commercial area. Hillside area as residential has been started a few century back, with the famous geotechnical engineer that are famous on research of slope and hillside area. Other than that, the other reasons of hillside as development area are based on to limitation area that are push developer to make hillside area as development area. The research aimed are to study the identification development limitation and policies of Slope Department on Hillside as development area. Futhermore, hillside area as development area in Malaysia are still in early stage with limited Slope Department that responsible of slope area make the awareness of risk and safety of hillside area to be development area in impugn and the responsible of the Slope Department to the hillside are being curious. The research objectives are to identify the implementation of safety feature of guideline to the procedure towards Hillside Development and to identify role and the scope of Local Authority Public Work Deparment (PWD), private agency that responsible to slope in Malaysia. The method of research are by observation on site, questionaire distribution and interview, the questionaire and interview to professional level of engineer in slope department. Parallelly with current law and regulation of the slope the slope department are taking serious of hillside area as development area. This serious view of slope will rised the awareness of risk to be taken and safety feature to add on hillside area as development area.